(untitled) (Research, Society and Development, 2020)
Introduction: Ozone is a potent antioxidant that acts as a precursor of various radicals, being indicated as a powerful therapy, assisting in the process of tissue healing. Objectives: The proposal of this study was to analyze material and structural properties via mechanical testing in tibias after application of ozone in bone defects produced surgically. Methods: Ten male 40-day old albino Wistar rats have been used, divided in two groups: control group and ozone group, this last one being treated with ozonized water in 25 µg/mL of concentration until the day of euthanasia. Trichotomy and longitudinal incision was conducted in the animals’ leg skin, exposing the tibia’s diaphysis of both antimers, and with help of a high rotation pen a flaw has been produced on the bone. After 60 days of surgery the animals were euthanized, and tibias were collected for biomechanical analysis. Results: The results of the biomechanical properties – structural and material – evidenced significant interactions through exposure to ozone, showing a diminished bone resistance in animals from the control group, observed by the decrease of the maximum force (N) needed to rupture the bone when compared to the value needed to break the bones of the animals from the ozone group, and the analysis of the morphometrical properties did not show any difference between both experimental groups. Conclusion: The use of ozone did not alter the morphological structures of the tibias, and the group which used ozone presented more resistance during mechanical testings, because the maximum force for the rupture of tibia was greater in this group.